Challenges to The Agricultural Development Policy Within A Subsistence Society: An Analysis Of The “Revolutionary Agricultural Policy” In South Western Sumba - Damar Waskitojati; Daniel Kameo; Pamerdi G Wiloso (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2019)
Employing a qualitative approach, this study attempts a critical investigation into the Kebijakan Revolusi Pertanian, ie. The Revolutionary Agricultural Policy, as it was developed by the Regional Government of South-western Sumba. During the years 2014-2019 it aimed to raise the agricultural economy, and thereby overcome the problem of poverty. The data for this research was procured through personal observation and deep interviews with sources such as key informants within the regional environment. These were reinforced with a number of planning documents and executive programs which comprise a secondary resource. The analysis of the Policy is done taking into account the relevant political, economic, technological and social aspects (PETS analysis), as well the innovations occurring during the course of this Policy. This study will demonstrate that the Policy has been, at least till now, incapable of having a significant impact on the agricultural economy, or the efforts to overcome poverty. The causes of this failure is the antagonism between the characteristics of the subsistence society found there and the weak institutional application of the policies employed.